Practice on the margins: reflections from the disability services sector. Issue 5 (2nd September 2016) - Ollerton, Janice Maree
Abstract: People labelled with disabilities are frequently positioned on the margins of society. Their positioning points to discursive practices underpinned by ableism which place and keep them there. In this article, a scenario based on actual events is used to reflect upon professional practice. The story is situated in a disability service, an area of practice located at the margins of the broader Human Services sector. The scenario raises important questions about how to establish respectful and productive relationships with people, develop person-centred practices which contribute to personal knowing and transformation, balance rights and risk, equitably manage relations of power and fulfil societal expectations on the provision of care. In this article, the author explores how reflection can negotiate meaning, challenge ableism and expose disablist practices. She seeks to open spaces where one might begin to re-story professional practices by centring the lived experiences of those who inhabit the margins.